2000
DOI: 10.1177/014272370002006003
|View full text |Cite
|
Sign up to set email alerts
|

Imitations and repetitions: what do children say following recasts?

Abstract: The current study investigated whether children revise their speech (i.e., imitate) or repeat their errors following negative evidence. In addition we examined how children's replies varied as a function of family setting. Fourteen children (2;3) were videotaped interacting with their mothers, fathers and siblings (4;1) in dyad, triad and tetrad settings. Analyses revealed that following recasts children were likely to revise their speech rather than repeat their original error. Without feedback, children repe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
2
1

Year Published

2004
2004
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(33 citation statements)
references
References 36 publications
1
29
2
1
Order By: Relevance
“…Negative evidence is potentially more informative, because child error and correct adult alternative contrast with one another in the discourse. There is evidence that such contrastive modeling not only occurs in the input to young children, but also is associated with improvements in the grammaticality of child speech (e.g., Farrar, 1992;Saxton, 1997Saxton, , 2000Saxton et al, 1998;Strapp, 1999;Strapp & Federico, 2000). The issue of whether negative evidence (error-contingent modeling) is a necessary component of language acquisition remains a moot point (for discussion, see Saxton, 2000).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Negative evidence is potentially more informative, because child error and correct adult alternative contrast with one another in the discourse. There is evidence that such contrastive modeling not only occurs in the input to young children, but also is associated with improvements in the grammaticality of child speech (e.g., Farrar, 1992;Saxton, 1997Saxton, , 2000Saxton et al, 1998;Strapp, 1999;Strapp & Federico, 2000). The issue of whether negative evidence (error-contingent modeling) is a necessary component of language acquisition remains a moot point (for discussion, see Saxton, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…A number of studies provide empirical evidence in support of the direct contrast hypothesis (e.g., Farrar, 1992;Saxton, 1997Saxton, , 2000Saxton, Backley, & Gallaway, in press;Saxton, Kulcsar, Rupra, & Marshall, 1998;Strapp, 1999;Strapp & Federico, 2000;Otomo, 2001;Chouinard & Clark, 2003). In particular, four key findings have emerged.…”
Section: Correct → Erroneous (C → E)mentioning
confidence: 99%
“…The following example 60 is typical (note that the child shows some evidence of accepting the recast). Although many studies [60][61][62][63][64][65][66][67][68][69][70][71][72] have shown that children selectively modify their utterances in response to recasts in this way, it would seem unlikely that they are sufficient to explain the retreat from error. The evidence summarized below indicates that children reject as ungrammatical certain uses of very low frequency and even novel verbs (in the latter case, based on their semantics), for which they cannot have received recasts during childhood.…”
Section: Adult Recastsmentioning
confidence: 99%
“…With respect to the former, Moerk (2000) noted that ''probably close to one hundred such studies exist supporting the existence of corrections'' (p. 117). Evidence for its effectiveness has continued to accumulate (e.g., Chouinard & Clark, 2003;Strapp, Bleakney, Helmick, & Tonkovich, 2008;Strapp & Federico, 2000).…”
Section: Mythmentioning
confidence: 99%